2013
DOI: 10.3390/ijerph10126701
|View full text |Cite
|
Sign up to set email alerts
|

A Cross-Cultural Comparison of Health Behaviors between Saudi and British Adolescents Living in Urban Areas: Gender by Country Analyses

Abstract: This study investigated the cross-cultural differences and similarity in health behaviors between Saudi and British adolescents. A school-based cross-sectional study was conducted at four cities in Saudi Arabia (Riyadh and Al-Khobar; N = 1,648) and Britain (Birmingham and Coventry; N = 1,158). The participants (14–18 year-olds) were randomly selected using a multistage stratified cluster sampling technique. Measurements included anthropometric, screen time, validated physical activity (PA) questionnaire and di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
32
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(32 citation statements)
references
References 59 publications
0
32
0
Order By: Relevance
“…Urbanization and related environmental determinants, including street networks engineered to discourage walking, may also have acted to deter physically active lifestyles in Saudi Arabia (Al-Hazzaa et al, 2013a). In addition, the hot and dusty environment adds another factor that discourages outdoor physical activity (Al-Hazzaa et al, 2013a).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Urbanization and related environmental determinants, including street networks engineered to discourage walking, may also have acted to deter physically active lifestyles in Saudi Arabia (Al-Hazzaa et al, 2013a). In addition, the hot and dusty environment adds another factor that discourages outdoor physical activity (Al-Hazzaa et al, 2013a).…”
Section: Discussionmentioning
confidence: 99%
“…Urbanization and related environmental determinants, including street networks engineered to discourage walking, may also have acted to deter physically active lifestyles in Saudi Arabia (Al-Hazzaa et al, 2013a). In addition, the hot and dusty environment adds another factor that discourages outdoor physical activity (Al-Hazzaa et al, 2013a). Conversely, the environment in Britain may be more conducive to outdoor physical activity and whilst the British cities used in this study are heavily urbanized, their urban design shows greater street connectivity, provision of pedestrianized areas and walkways than is the case for Saudi Arabia (International Monetary fund, 2012).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although they are two different behavioral domains representing two separate constructs, not merely functional opposites, they have an independent association with the various risk factors of non-communicable diseases [15,16].The two behavioral tendencies such as low physical activity and more sedentary lifestyle can have a significant influence on their inherent sociocultural factors. Recent studies showed that childhood lifestyle behavior may be influenced by socio-cultural and environmental factors [17,18]. Therefore, the patterns of energy expenditure may vary according to their diverse experiences of lifestyle, especially in developed countries when compared to developing countries.…”
Section: Introductionmentioning
confidence: 99%
“…A late study has uncovered that young people who utilize the Internet pathologically will probably create melancholy than the individuals who don't. Obsessive (uncontrolled or absurd) utilization of Internet has been connected with relationship issues, physical sick wellbeing, forceful practices and other psychiatric side effects [69][70][71][72][73][74][75][76][77][78][79][80][81][82][83].…”
Section: Correspondence and Online Social Networkingmentioning
confidence: 99%